Efficacy of fimasartan/hydrochlorothiazide combination in hypertensive patients inadequately controlled by fimasartan monotherapy - Rhee, Moo-Yong (Drug Des Devel Ther, 2015)
BACKGROUND: The study reported here compared the blood pressure (BP)-lowering efficacy of fimasartan alone with that of fimasartan/hydrochlorothiazide (HCTZ) combination in patients whose BP goal was not achieved after 4 weeks of treatment with once-daily fimasartan 60 mg. METHODS: Patients with sitting diastolic blood pressure (siDBP) ≥90 mmHg with 4 weeks of once-daily fimasartan 60 mg were randomly assigned to receive either once-daily fimasartan 60 mg/HCTZ 12.5 mg or fimasartan 60 mg for 4 weeks. After 4 weeks, the dose was increased from fimasartan 60 mg/HCTZ 12.5 mg to fimasartan 120 mg/HCTZ 12.5 mg or from fimasartan 60 mg to fimasartan 120 mg if siDBP was ≥90 mmHg. RESULTS: Of the 263 randomized patients, 256 patients who had available efficacy data were analyzed. The fimasartan/HCTZ treatment group showed a greater reduction of siDBP compared to the fimasartan treatment group at Week 4 (6.88±8.10 mmHg vs 3.38±7.33, P=0.0008), and the effect persisted at Week 8 (8.67±9.39 mmHg vs 5.02±8.27 mmHg, P=0.0023). Reduction of sitting systolic BP in the fimasartan/HCTZ treatment group was also greater than that in the fimasartan treatment group (at Week 4, 10.50±13.76 mmHg vs 5.75±12.18 mmHg, P=0.0069 and, at Week 8, 13.45±15.15 mmHg vs 6.84±13.57 mmHg, P=0.0007). The proportion of patients who achieved a reduction of siDBP ≥10 mmHg from baseline and/or a mean siDBP <90 mmHg after 4 weeks of treatment was higher in the fimasartan/HCTZ treatment group than in the fimasartan treatment group (53.6% vs 39.8%, P=0.0359). The overall incidence of adverse drug reaction was 11.79% with no significant difference between the treatment groups. CONCLUSION: The combination treatment of fimasartan and HCTZ achieved better BP control than fimasartan monotherapy, and had comparable safety and tolerance to fimasartan monotherapy.